183k views
22 votes
Evaluate
A)9
B)-9
c) 729
d) -729

Evaluate A)9 B)-9 c) 729 d) -729-example-1

1 Answer

14 votes

The correct option is c) 729

Step-by-step explanation :-


\frac{1}{ {3}^( - 2) {x }^( - 4) {y}^(2) }


= \frac{ {3}^(2) {x}^(4) }{ {y}^(2) }

Now , we just need to substitute " x = 3 " and " y = -1 " in the equation above.


⇢ \frac{ {3}^(2) {(3)}^(4)}{ {( - 1)}^(2) }


= (3 * 3 * 3 * 3 * 3 * 3)/(( -1) * ( - 1))


= (729)/(1)


= \underline { \boxed{ 729}}

User Cyberz
by
6.3k points